Inkjet printing of resistively loaded FSS for microwave absorbers - Cahill, Robert; Zabri @ Suhaimi, Siti Normi; Conway, Gareth A.; Schuchinsky, Alexander G. (Institution of Engineering and Technology, 2015)
Inkjet printing is proposed as a means to create the resistively loaded elements of a frequency selective surface(FSS) which suppresses radar backscatter when placed above a metal ground plane. Spectral transmission and reflection measurements from 9 to 18 GHz show that the dot density of the printed features and the volume ratio of an aqueous vehicle and nano-silver (Ag) ink mixture can be selected to obtain surface resistances in the range 1.2 – 200 Ω/sq.